MUHAMMADIYAH NAZHIR ORGANIZATION Analysis of Waqf Management and Development in Cianjur - Cucu Solihah; Dedi Mulyadi; Hilman Nur (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Throughout the history of human civilization, waqf has been able to prove its considerable contribution to religion, humanity, economy, and society. Waqf management and development brings positive impact on society if it is administered by waqf goal-oriented nazir, one of which is managed by Muhammadiyah organization. Their assets grows bigger each year by focusing on social program as their main strategy. This study employed normative juridical approach by descriptive analysis. The data source of this research is primary source from interview with the local leaders of Muhammadiyah and waqifs.Keywords: welfare, nazir, utilization